Gender differences in the prevalence and clustering of multiple health risk behaviours in young adults. (22nd April 2016) - Kritsotakis, George; Psarrou, Maria; Vassilaki, Maria; Androulaki, Zacharenia; Philalithis, Anastas E.
Abstract: Aims: To estimate the sex‐stratified prevalence and clustering of 14 behavioural and metabolic health risk factors in emerging adulthood. Background: The high prevalence and the clustering of risk factors multiply health consequences and increase the threat to the future health and quality of life of young adults. Design: Descriptive cross‐sectional study. Methods: During November‐December 2012, we assessed 14 lifestyle characteristics of 1058 1st year university students' that were classified as: healthy (score = 0), unhealthy (score = 1) and high‐risk unhealthy (score = 2). We subsequently created a Multiple Health Risk Behaviours Index by summing the score of each behaviour adjusted to 0‐100. Results: Only 0·3% of the students had one risk behaviour and 21·3% (male: 31·5%; female: 12·6%) had ≥10 of 14. Male students had higher risk index score. In adjusted regression analyses, female students had higher odds of reporting healthier behaviours in oral hygiene (tooth brushing), red meat and junk food consumption, binge drinking, cannabis/hashish/marijuana use and lower number of sexual partners and Body Mass Index. Male students reported higher physical activity. No statistically significant gender differences were noted for screen time/sedentary behaviours, condom use, smoking, sunburns, breakfast and fruit and vegetable consumption. Conclusion: Although health‐compromising behaviours are highly prevalent in both men and women, they are gender‐related, with males engaging in more health risk behaviours than females. Preventive interventions may need to focus on gender‐informed approaches when targeting multiple health risk behaviours.